Autonomous interface selection for multi-radio d2d communication - Paul, Rajib; Choi, Young June (IEEE Access, 2019)
Device-to-device communications are considered as a key feature to enhance the performance of the fifth generation (5G) wireless networks. Several radio access technologies such as LTE Direct, Bluetooth, Wi-Fi, and ZigBee are expected to provide the opportunity of D2D communications. Therefore, it is possible to choose any of them autonomously to establish a D2D link. The primary focus of this work is to investigate the radio interface selection, where end users select an interface opportunistically among different available radio interfaces to establish outband D2D connectivity against interference. We model a non-cooperative game to select a radio interface for D2D users to minimize their communication cost. We have investigated Nash equilibrium in the game and argue that without any co-operation users can achieve a balanced strategy. In our model, each pair selects a radio interface based on a utility function that associates communication performance and cost. Finally, we propose three heuristic algorithms: Social, Greedy, and Local, that achieve Nash equilibrium with different information. Event-driven simulation experiments are then conducted to evaluate the utility and cost of the equilibrium strategy. Our results confirm that the proposed schemes can increase the utility, lower the cost, and lead to higher efficiency in terms of achievable throughput per consumed energy.
Keywords: Achievable throughputs; Communication performance; D2D communications; Device-to-Device communications; Event-driven simulations; Multiple radios; Nash equilibria; Radio access technologies; D2D communications; game theory; multiple radio interfaces; Nash equilibrium